Teaching, Research and Academic Careers An Analysis of the Interrelations and Impacts - Checchi, Daniele; Jappelli, Tullio; Uricchio, Antonio (Springer Nature, 2022)
This open access book evaluates research quality, quality of teaching and the relationship between the two through sound statistical methods, and in a comparative perspective with other European countries. In so doing, it covers an increasingly important topic for universities that affects university funding. It discusses whether university evaluation should be limited to a single factor or consider multiple dimensions of research, since academic careers, teaching and awarding degrees are intertwined. The chapters included in the book evaluate teaching and research, also taking the gender dimension into account, in order to understand where and when gender discrimination occurs in assessment. Divided into five sections, the book analyses the administrative data on the determinants of career completion of university students; increasing precariousness of academic careers, especially of young researchers; methods designed to assess research productivity when co-authorship and team production are becoming the standard practice; and interrelations between students' achievements and teachers' careers driven by research assessment. It brings together contributions from a large group of economists, statisticians and social scientists working under a project sponsored by ANVUR, the Italian agency for the evaluation of teaching and research of academic institutions. From an international perspective, the findings in this book are particularly interesting because despite low tuition costs, tertiary education in Italy has relatively low enrolment rates and even lower completion rates compared to those in other European and American countries. This book is of interest to researchers of the sociology of education, education policy, public administration, economics and statistics of education, and to administrators and policy makers working in the area of higher education.